2014
DOI: 10.1055/s-0034-1383023
|View full text |Cite
|
Sign up to set email alerts
|

Aktueller Status der Hüft- und Knieendoprothetik in Deutschland – Ergebnisse einer bundesweiten Umfrage

Abstract: The treatment procedures for elective hip and knee replacement are very heterogeneous in German hospitals. The quality of the clinical outcome cannot be related to a single procedure; in fact the choice and complementary interaction of interventions are essential for improving patient care. These results provide first important evidence to which extent organisational structures and treatment procedures affect patient care and length of stay. Therefore, the analyses show relevant indications for an optimised st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
7
0
5
Order By: Relevance
“…j Surgical procedures Jaschinski et al (2014) conducted a nationwide survey in Germany on elective total hip and knee arthroplasty based on data from hospitals that recorded a minimum of 100 primary operations in their 2010 quality reports. Chief physicians from 694 orthopedics/trauma surgery departments and the respective anesthetists were contacted in writing with the aim of gaining insight into treatment processes and medical approaches as well as obtaining suggestions for optimizing care.…”
Section: J Comorbidity and Perioperative Riskmentioning
confidence: 99%
See 4 more Smart Citations
“…j Surgical procedures Jaschinski et al (2014) conducted a nationwide survey in Germany on elective total hip and knee arthroplasty based on data from hospitals that recorded a minimum of 100 primary operations in their 2010 quality reports. Chief physicians from 694 orthopedics/trauma surgery departments and the respective anesthetists were contacted in writing with the aim of gaining insight into treatment processes and medical approaches as well as obtaining suggestions for optimizing care.…”
Section: J Comorbidity and Perioperative Riskmentioning
confidence: 99%
“…31.8 % of the hospitals contacted responded. 303 questionnaires from 221 hospitals were statistically evaluated, based on which the authors concluded that the study was representative (Jaschinski et al 2014). …”
Section: J Comorbidity and Perioperative Riskmentioning
confidence: 99%
See 3 more Smart Citations